STUDENTS’ DIFFICULTIES IN SPEAKING ENGLISH AT THE SECOND GRADE OF MTs NEGERI 1 BUNGO - Suryani, Hilma; Abadi, Ayuliamita; Tika, Herni; Mayazila, Wafiq (JR-ELT (Journal of Research in English Language Teaching), 2020)
This research sought to identify students' difficulties in speaking English and the root causes of those difficulties. This research was carried out in MTsN 1 Bungo. The research design utilizes qualitative descriptive methodology. This investigation focuses on the second-grade MTsN 1 Bungo students. The data for this research were gathered through observation and interviews. The researcher determined, based on the findings and discussion, that speaking English presents and is accompanied by a number of difficulties and causes of difficulty. The linguistic difficulties the student encountered when speaking English were a lack of pronunciation, vocabulary, and grammar. When speaking English, students struggle with a lack of confidence, shyness, and apprehensiveness. pronunciation difficulties predominate among difficulties. The majority of students stated that they are afraid of pronouncing English words incorrectly. Student difficulties are caused by a fear of making a blunder.